2021
DOI: 10.3389/fmed.2021.713599
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Band Keratopathy in Aphakic Eyes With Silicone Oil Tamponade for Open-Globe Injuries: A Multicenter Case-Control Study

Abstract: Band keratopathy (BK) is a common complication in aphakic eyes with silicone oil tamponade for open-globe injury (OGI), characterized by the grayish-white opacities in the cornea, resulting in a significantly decreased vision when extending to the visual axis. To identify the risk factors for BK in aphakic eyes following vitreoretinal surgical treatment with silicone oil tamponade for OGIs, we performed a multicenter case-control study. The incidence of BK was 28% (28/100 eyes). The multivariate binary logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
(22 reference statements)
1
5
0
Order By: Relevance
“…Silicone oil is either removed 3–6 months postoperatively or long-term silicone tamponade is performed depending on various diseases and situations. The observation is the same as that in several studies, which demonstrated that silicone oil tamponade is an important risk factor for band keratopathy ( 6 , 7 , 37 ) even after removal ( 38 ). Although the mechanism of band keratopathy is multifactorial, many studies have shown that silicone oil plays a significant role in the development of band keratopathy ( 7 , 37 ) and that the tissue toxicity of silicone oil or pH changes due to from decreased flow across the corneal tissue may be associated with band keratopathy development ( 39 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Silicone oil is either removed 3–6 months postoperatively or long-term silicone tamponade is performed depending on various diseases and situations. The observation is the same as that in several studies, which demonstrated that silicone oil tamponade is an important risk factor for band keratopathy ( 6 , 7 , 37 ) even after removal ( 38 ). Although the mechanism of band keratopathy is multifactorial, many studies have shown that silicone oil plays a significant role in the development of band keratopathy ( 7 , 37 ) and that the tissue toxicity of silicone oil or pH changes due to from decreased flow across the corneal tissue may be associated with band keratopathy development ( 39 ).…”
Section: Discussionsupporting
confidence: 89%
“…Histological analysis of affected corneas shows a fine granular calcification in the superficial cornea including the Bowman’s membrane and deep-situated calcium plaques involving the anterior stroma ( 1 , 3 ). A variety of factors are associated with band keratopathy, including chronic ocular conditions such as uveitis ( 4 , 5 ), silicon oil retention ( 6 , 7 ) and phthisis bulbi; and systemic condition such as diabetes mellitus (DM), chronic kidney disease (CKD) ( 8 ), elevated serum phosphate levels and increased serum calcium levels that are possibly related to secondary hyperparathyroidism ( 9 – 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of BK can be multifactorial, oftentimes resulting from chronic inflammation, corneal ulcers, chemical burns and multiple surgeries. 37 However, it has been reported that SO can contribute to the development of BK, 38 which usually occurs following prolonged SO contact with the corneal endothelium, [38][39][40] with an incidence of 6% to 28%. 38,39,41,42 SO blocks the transport of nutrients from the aqueous humor, leading to a lower endothelial metabolic rate.…”
Section: ' Diabetic Keratopathymentioning
confidence: 99%
“…37 However, it has been reported that SO can contribute to the development of BK, 38 which usually occurs following prolonged SO contact with the corneal endothelium, [38][39][40] with an incidence of 6% to 28%. 38,39,41,42 SO blocks the transport of nutrients from the aqueous humor, leading to a lower endothelial metabolic rate. 43 This results in a reduction of lactic acid production, with no change in the rate of carbon dioxide loss due to constant evaporation.…”
Section: ' Diabetic Keratopathymentioning
confidence: 99%
See 1 more Smart Citation